OpenCV for secret agents : use OpenCV in six secret projects to augment your home, car, phone, eyesight, and any photo or drawing /: use OpenCV in six secret projects to augment your home, car, phone, eyesight, and any photo or drawing. (2015) - Howse, Joseph
No abstract available